Online Shop dalam Perspektif Hukum Ekonomi Syariah: Analisis Prinsip, Akad, dan Legalitas Transaksi Digital: Online Shops in the Perspective of Islamic Economic Law: Principles, Contracts, and the Legality of Digital Transactions - Aqil Husein Almanuri (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2026)
The rapid development of digital technology has significantly transformed trading practices through the emergence of online shop systems. This phenomenon raises questions regarding the compatibility of digital transaction mechanisms with the principles of Islamic economic law. This study aims to analyze the concepts, principles, and implementation of contracts in online shop transactions from the perspective of Islamic economic law. This research employs a normative legal research method using conceptual and statutory approaches, particularly referring to classical fiqh muamalah literature and fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN–MUI). The findings indicate that online shop practices are generally permissible in Islam as long as they fulfill the pillars and conditions of contracts, involve lawful and clearly defined objects of transaction, and are conducted based on mutual consent between the parties. Furthermore, digital transactions must be free from elements of gharar (uncertainty), riba (usury), fraud, and injustice. However, the study also identifies potential risks in digital transactions, such as information asymmetry, unclear contractual structures, and the use of hybrid or multi-contract schemes that may lead to Sharia compliance issues if not properly regulated. In practice, online shop transactions may involve several types of contracts such as bai’, salam, istishna’, wakalah, and ijarah, depending on the mechanisms of payment, ordering, and delivery. These findings suggest that digital commerce can operate in accordance with Sharia principles when conducted transparently, fairly, and responsibly, and supported by adequate regulatory frameworks and digital literacy to ensure consistent Sharia compliance.